Análisis estadístico de la producción de un biocontrolador de la mosca blanca en plantas de frijol bajo invernadero (2011)
The greenhouse whiteﬂy Trialeurodes vaporariorum, is one of the majorcroppestsin Colombia. Several strategies have been used in order to control this pest,being one of them the use of natural enemies, which is an environmentally friendly strategy. The parasitic wasp Encarsia formosaacts as a natural enemy of whiteﬂies and it have been documented as one of the most successful cases of biological control around the world.In the last years, the Nueva Granada Military University has established a half-commercial production unit of this wasp with purpose of commercial and agricultural distribution in the savannah of Bogota´. In order to optimize the mass rearing process, a statistical analysis was performed using the production data between August and December of 2010. Using this information, the maximum, minimum and mean level of production was established. Later, an experimental faze was performed in order to ﬁnd the relation of the leaf area of a bean plant attacked and the proportion of pest infestation, the oviposition preference of E. formosa in a bean leaf infested with T. vaporariorum and the relation of the number of wasp used in the mass rearing process and the number of wasp produced. The data were processed using the statistical package SAS INSTITUTE INC (2008). There isn’t a relation between the leaf area and the number of whiteﬂies in a leaf but there is a feeding preference towards the center of the leaf. Finally, regression analysis was made between the waspparasitization eﬃciency and the population density of the wasp. In order to improve the production is necessary release a lower number of wasps rather than the originally established.